Modelling a market stability reserve in carbon markets - Anne Schopp; William Acworth; Daniel Huppmann; Karsten Neuhoff (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
We examine under which conditions a cap-and-trade mechanism can deliver a dynamically efficient abatement pathway and contribute to a robust investment framework. For this we develop a numerical dynamic partial-equilibrium model that includes differentiated objective functions of different market participants for holding emission allowances based on their banking strategy. If the surplus of allowances is large, as currently observed in the European Union Emissions Trading System, the equilibrium market outcome can deviate from an efficient abatement pathway and performance of the policy is reduced against a set of key criteria (dynamic efficiency, price credibility, price consistency, and robustness to shocks). The model is applied to assess design options of quantity and price based market stability reserves as discussed in Europe. Both price and quantity based mechanisms can improve the performance of the EU ETS against key criteria.
Keywords: D84; G18; Q48; 330; Computational Model; Emissions trading; Environmental Regulation; Market stability reserve